A method for preparing a low-temperature densified hexagonal boron nitride ceramic ink direct writing 3D printing

CN122977852APending Publication Date: 2026-10-27CHINA TOBACCO HEBEI INDUSTRIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611361642.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]针对现有六方氮化硼陶瓷增材制造过程中存在的浆料粘弹性不足、打印结构保持能力差以及烧结温度高、致密化困难等问题,本发明提供一种低温致密化六方氮化硼陶瓷墨水及其直写3D打印制备方法

Benefits of technology

本发明通过引入微细尺寸六方氮化硼颗粒,利用其较大的比表面积和较高表面活性,增强颗粒间相互作用,构建稳定的浆料弱网络结构,提高陶瓷墨水的粘度、储能模量以及屈服应力,使其满足墨水直写3D打印过程中连续挤出和结构保持需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977852A_ABST
    Figure CN122977852A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of ceramic additive manufacturing, and discloses a low-temperature densification hexagonal boron nitride ceramic ink and an ink direct-writing 3D printing and boron nitride ceramic piece preparation method. The ceramic ink comprises, in parts by weight, 45-65 parts of hexagonal boron nitride ceramic particles with a particle size D50 of 0.5-5 microns, 3-8 parts of polyvinyl alcohol, 0.1-2 parts of a dispersing agent and 25-45 parts of deionized water. By adjusting the particle size and the proportion of the slurry components, the ceramic ink has good shear thinning and viscoelastic properties, the continuity of the silk strip in the 3D printing process is improved, and the structure maintaining capacity is improved. The high specific surface area and surface activity of the micro-particles can promote particle contact, interface diffusion and sintering neck formation, realize low-temperature densification sintering of the hexagonal boron nitride ceramic at 800-1000 DEG C, and prepare a hexagonal boron nitride ceramic piece which is complete in structure, stable in size and high in mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of advanced ceramic additive manufacturing technology, and in particular to a method for preparing low-temperature densified hexagonal boron nitride ceramic ink by direct writing 3D printing. Background Technology

[0002] Hexagonal boron nitride (h-BN) is a layered ceramic material composed of boron and nitrogen. Because its crystal structure is similar to graphite, it is often called "white graphite." Hexagonal boron nitride possesses excellent high-temperature stability, good thermal conductivity, high electrical insulation properties, a low coefficient of friction, and excellent chemical inertness, making it valuable for applications in aerospace thermal protection, high-temperature insulating components, electronic packaging heat dissipation, and the manufacture of advanced ceramic structures.

[0003] Traditional hexagonal boron nitride ceramics are mainly prepared using methods such as dry pressing, hot pressing sintering, and cold isostatic pressing. The forming process relies on mold constraints. While this allows for the large-scale manufacturing of simple ceramic parts, it is difficult to produce ceramic components with complex curved surfaces, porous structures, lightweight lattice structures, and complex internal channels. Furthermore, the long manufacturing cycle and high cost of molds limit the design freedom and rapid manufacturing capabilities of hexagonal boron nitride ceramics.

[0004] In recent years, the development of additive manufacturing technology has provided a new technological path for the fabrication of complex ceramic structures. Among them, Direct Ink Writing (DIW) 3D printing technology can realize the integrated fabrication of complex three-dimensional structures by controlling the layer-by-layer extrusion deposition of high-solids ceramic slurry. It has advantages such as simple equipment, strong material adaptability, and high degree of freedom in structural design, and is particularly suitable for the preparation of honeycomb structures, lattice structures, and lightweight thermal management components.

[0005] However, the preparation of hexagonal boron nitride ceramics using DIW technology still faces many challenges. On the one hand, hexagonal boron nitride particles have strong layered structure characteristics and low surface activity. In water-based slurries, the interparticle interactions are weak, making it difficult to form a stable spatial network structure. This results in insufficient viscoelastic properties of the ceramic ink, leading to problems such as filament collapse, blurred boundaries, and poor structure retention during printing. On the other hand, to obtain higher ceramic density, it is necessary to increase the solid content of the slurry. However, high-solids-content hexagonal boron nitride slurries are prone to agglomeration and flow hindrance, reducing the stability of the printing process.

[0006] Furthermore, due to its strong covalent bond structure and low self-diffusion capability, hexagonal boron nitride typically requires temperatures above 1600℃ to achieve a high degree of densification in traditional sintering processes. High-temperature sintering not only increases energy consumption but also easily causes grain growth and structural shrinkage deformation, limiting the additive manufacturing applications of complex-structured hexagonal boron nitride ceramics. Therefore, developing a hexagonal boron nitride ceramic ink and its preparation method that can balance DIW printing performance and low-temperature densification capabilities is of great significance for advancing the additive manufacturing of complex-structured boron nitride ceramics. Summary of the Invention

[0007] To address the problems of insufficient viscoelasticity of slurry, poor ability to retain printed structures, high sintering temperature, and difficulty in densification in existing hexagonal boron nitride ceramic additive manufacturing processes, this invention provides a low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing low-temperature densified hexagonal boron nitride ceramic ink via direct writing 3D printing, wherein the ceramic ink is composed of hexagonal boron nitride ceramic powder, binder, dispersant, and deionized water, with the following mass percentages of each component: Hexagonal boron nitride ceramic powder: 45%–65%; Adhesive: 2%–8%; Dispersant: 0.1%–2%; Deionized water: 25%–45%.

[0009] The hexagonal boron nitride ceramic powder is a fine-particle hexagonal boron nitride powder with a particle size D50 of 0.5–25 μm.

[0010] The ceramic ink is formed by ink direct writing 3D printing and then sintered at low temperature to obtain a dense hexagonal boron nitride ceramic structural component.

[0011] Preferably, the particle size D50 of the hexagonal boron nitride ceramic powder is 0.5 to 5 μm.

[0012] Due to their high specific surface area and surface activity, fine hexagonal boron nitride particles can enhance the interaction between particles, improve the viscosity, storage modulus and yield stress of ceramic ink, and enable the extruded filament to have good continuity and shape retention during the printing process.

[0013] Preferably, the adhesive is a water-soluble polymeric adhesive, including at least one of polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), hydroxypropyl cellulose (HPC), and carboxymethyl cellulose (CMC); preferably polyvinyl alcohol (PVA).

[0014] Preferably, the dispersant is at least one of sodium polyacrylate, polycarboxylate, polyether dispersant, polyethylene glycol dispersant, and anionic surfactant.

[0015] Preferably, it includes the following steps: A. Preparation of ceramic ink Fine hexagonal boron nitride powder was pre-dispersed in deionized water, followed by the addition of binder and dispersant. After being mechanically stirred and mixed evenly, the mixture was transferred to a ball mill for dispersion treatment to obtain a uniform and stable hexagonal boron nitride ceramic ink.

[0016] The ball milling speed was 200–400 r / min; the ball milling time was 2–6 h. The resulting ceramic ink was then subjected to vacuum degassing for 10–30 min to remove internal air bubbles.

[0017] B. Ink-to-Write 3D Printing The prepared hexagonal boron nitride ceramic ink is loaded into an ink direct writing 3D printing device and three-dimensional structure is formed by air pressure extrusion.

[0018] Printing parameters include: nozzle diameter: 0.2~0.6mm; printing pressure: 0.1~0.5MPa; printing speed: 5~20mm / s; layer thickness: 0.1~0.4mm.

[0019] After printing, a hexagonal boron nitride ceramic green body is obtained.

[0020] C. Drying and low-temperature sintering The printed ceramic green body is dried and then degreased and sintered.

[0021] The drying temperature is 40–80℃; the drying time is 6–24 hours.

[0022] The sintering process includes: First stage: Raise the temperature from room temperature to 400-600℃ at a rate of 1-3℃ / min and hold for 60-180min; The second stage involves heating from 400–600℃ to 800–1000℃ at a rate of 0.3–2℃ / min and holding for 60–240 min. The temperature is then naturally cooled to room temperature to obtain a low-temperature densified hexagonal boron nitride ceramic structural component.

[0023] Preferably, the hexagonal boron nitride ceramic ink has shear-thinning rheological properties, exhibiting high viscosity at low shear rates and decreasing viscosity at high shear rates, thereby meeting the requirements for extrusion printing.

[0024] Preferably, during the sintering process, the fine hexagonal boron nitride particles increase the particle contact area, enhance interfacial diffusion behavior, and promote the formation of sintering necks, thereby improving the densification of the ceramic structure and enabling the hexagonal boron nitride ceramic to obtain a stable structure in the temperature range of 800–1000°C.

[0025] Preferably, the prepared hexagonal boron nitride ceramic structural component includes at least one of the following: honeycomb structure, lattice structure, porous thermal insulation structure, complex curved surface structure, and thermal management structure.

[0026] Preferably, the prepared hexagonal boron nitride ceramic structural component has a relative density of over 80% and a flexural strength of over 30 MPa.

[0027] Compared with the prior art, the present invention has the following beneficial effects: This invention introduces fine-sized hexagonal boron nitride particles, which, by utilizing their large specific surface area and high surface activity, enhance the interaction between particles, construct a stable weak network structure in the slurry, and improve the viscosity, storage modulus, and yield stress of the ceramic ink, so as to meet the requirements of continuous extrusion and structure retention in the ink direct-write 3D printing process.

[0028] Meanwhile, fine hexagonal boron nitride particles can shorten the diffusion distance between particles during sintering, increase the interfacial diffusion driving force, promote particle contact, sintering neck formation and structural densification, and realize low-temperature sintering of hexagonal boron nitride ceramics in the temperature range of 800 to 1000℃, thereby improving the structural integrity and mechanical properties of printed ceramics. Attached Figure Description

[0029] Figure 1 This is the TG-DSC analysis chromatogram of boron nitride according to the present invention; Figure 2 XRD patterns of boron nitride at different temperatures according to the present invention; Figure 3 This is the cloud map and histogram of size deviation distribution of the present invention. Detailed Implementation

[0030] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.

[0031] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative effort are all within the scope of protection of the present invention.

[0032] It should be noted that, where no specific technology or conditions are specified in the embodiments, the technology or conditions described in the publicly available literature in this field or in accordance with the product manual shall apply.

[0033] Examples 1-4 The present invention provides the following group allocation examples for Examples 1-4 as shown in Table 1 (in mass percentage).

[0034] In this example, the hexagonal boron nitride powder was controlled by different particle sizes. Example 1 used fine hexagonal boron nitride particles with a particle size D50=2μm, Example 2 used hexagonal boron nitride particles with a particle size D50=1μm, Example 3 used hexagonal boron nitride particles with a particle size D50=5μm, and Example 4 used hexagonal boron nitride particles with a particle size D50=2μm and adjusted the binder content.

[0035] Comparative Examples 1-3 To investigate the effect of hexagonal boron nitride particle size on ink performance and low-temperature densification behavior, hexagonal boron nitride with different particle sizes were set as comparative examples.

[0036] Table 1. Distribution ratio (mass percentage) of each group in the example. Table 2. Distribution ratios of each group in the comparative example. The preparation steps for hexagonal boron nitride ceramic ink are as follows: Step 1: Preparation of Ceramic Ink According to the component ratios in Tables 1 and 2, hexagonal boron nitride powder was pre-dispersed in deionized water, followed by the addition of a dispersant and polyvinyl alcohol binder. The components were then thoroughly mixed using mechanical stirring. The resulting slurry was transferred to a planetary ball mill for further dispersion at 250 rpm for 4 hours, yielding a uniform and stable hexagonal boron nitride ceramic ink. Subsequently, the ceramic ink was placed in a vacuum environment for 20 minutes to remove air bubbles and improve printing stability.

[0037] Step 2: Ink Direct Writing 3D Printing The hexagonal boron nitride ceramic ink prepared in step one was loaded into an ink-to-ink 3D printer and deposited layer by layer via pneumatic extrusion. The printing parameters were as follows: nozzle diameter: 0.41 mm; printing pressure: 0.25–0.35 MPa; printing speed: 10 mm / s; layer thickness: 0.25 mm. The printed structures were a hollow lattice structure and a cuboid test sample. After printing, the resulting green body was dried in a 60°C oven for 12 hours to obtain the hexagonal boron nitride ceramic green body.

[0038] Step 3: Low-temperature degreasing and sintering The hexagonal boron nitride ceramic green body obtained in step two was placed in a tube furnace for debinding and sintering. The sintering procedure was as follows: First, the temperature was raised from room temperature to 400℃ at a rate of 2℃ / min and held for 120 min to allow the organic binder to fully decompose; then, the temperature was raised from 400℃ to 800℃ at a rate of 1℃ / min and held for 120 min; finally, the temperature was raised from 800℃ to 900–1000℃ at a rate of 1℃ / min and held for 120 min, followed by natural cooling to room temperature. This resulted in a low-temperature densified hexagonal boron nitride ceramic structural component.

[0039] Performance testing The present invention performs performance tests on the hexagonal boron nitride ceramic inks, green bodies, and sintered samples prepared in Examples 1-4 and Comparative Examples 1-3.

[0040] Among them, the rheological properties of the slurry were tested using a rotational rheometer, and steady-state shear scanning was performed at 25℃ to analyze the variation of slurry viscosity with shear rate.

[0041] The viscoelastic properties of the slurry were tested using a dynamic oscillation mode to obtain the storage modulus G′ and loss modulus G″.

[0042] The density of the sintered samples was tested using Archimedes' method of water displacement. The flexural strength was tested using the three-point bending test method at a loading rate of 0.5 mm / min.

[0043] The test results are shown in Table 3.

[0044] Table 3 Performance comparison of each embodiment and comparative example As can be seen from the results in Table 3, the particle size of hexagonal boron nitride has a significant impact on the rheological properties and sintering densification behavior of ceramic ink.

[0045] Example 1 uses fine hexagonal boron nitride particles with a D50 of 2 μm to prepare ceramic ink. The slurry exhibits high viscosity and storage modulus, maintaining a continuous filament structure during extrusion, resulting in a complete printed sample surface without significant collapse. Example 2 uses even smaller hexagonal boron nitride particles. Due to the further increase in particle specific surface area, the interparticle interaction is enhanced, further improving the viscoelastic properties of the slurry. Simultaneously, the increased particle contact area during sintering promotes interfacial diffusion and sintering neck formation, thus achieving higher density and mechanical properties.

[0046] Compared to Example 1, Comparative Example 1 used 10μm hexagonal boron nitride particles. Due to the increased particle size, the specific surface area decreased, and the particle effect within the slurry weakened, resulting in a decrease in viscosity and storage modulus. This reduced the structure retention capacity during printing, and the insufficient sintering driving force led to a decrease in the density of the sintered sample. Comparative Example 2 used 25μm hexagonal boron nitride particles, further increasing the particle size. This made it difficult for the slurry to form a stable network structure, resulting in edge collapse after printing. Furthermore, due to the increased particle diffusion distance, it was difficult to achieve sufficient densification at 900℃, leading to a significant decrease in sample strength.

[0047] In addition, through Figure 1 TG-DSC analysis revealed that the hexagonal boron nitride ceramic ink exhibits a heat effect of adsorbed water removal around 100°C and a significant change in heat flow around 850°C, corresponding to the removal of binder residues, rearrangement of particle interfaces, and sintering densification processes. Figure 2 XRD analysis results show that as the sintering temperature increases, the peak intensity of the hexagonal boron nitride (002) crystal plane gradually changes, indicating that the particle packing state and the ordered crystal structure are adjusted during the heat treatment process, which further promotes the densification of the ceramic structure. Figure 3 The cloud map and the histogram of dimensional deviation distribution are derived from... Figure 3 It can be seen that the overall dimensional deviation of the sample is mainly concentrated within the range of ±0.16mm, with most areas having a deviation of less than ±0.08mm. Only the edge positions have slight deviations, indicating good overall forming accuracy. This verifies the manufacturability and dimensional controllability of the boron nitride DIW process.

[0048] In summary, this invention utilizes the size effect of fine hexagonal boron nitride particles to optimize the rheological properties of the slurry and control the densification during low-temperature sintering in ink-direct writing 3D printing, thereby obtaining hexagonal boron nitride ceramic structural parts with complete structure and excellent mechanical properties.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Modifications or substitutions made by those skilled in the art to the above embodiments without departing from the essence of the technical solutions of the present invention should be included within the scope of protection of the present invention.

[0050] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A low-temperature densified hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method, characterized in that, The ceramic ink is composed of hexagonal boron nitride ceramic powder, binder, dispersant, and deionized water, with the following mass percentages of each component: Hexagonal boron nitride ceramic powder: 45%–65%; Adhesive: 2%–8%; Dispersant: 0.1%–2%; Deionized water: 25%–45%. The hexagonal boron nitride ceramic powder is a fine-particle hexagonal boron nitride powder with a particle size D50 of 0.5–25 μm. The ceramic ink is formed by ink direct writing 3D printing and then sintered at low temperature to obtain a dense hexagonal boron nitride ceramic structural component.

2. The low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method as described in claim 1, characterized in that: The preferred particle size D50 of the hexagonal boron nitride ceramic powder is 0.5–5 μm. Due to their high specific surface area and surface activity, fine hexagonal boron nitride particles can enhance the interaction between particles, improve the viscosity, storage modulus and yield stress of ceramic ink, and enable the extruded filament to have good continuity and shape retention during the printing process.

3. The low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method as described in claim 1, characterized in that: The adhesive is a water-soluble polymeric adhesive, including at least one of polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), hydroxypropyl cellulose (HPC), and carboxymethyl cellulose (CMC); preferably polyvinyl alcohol (PVA).

4. The low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method as described in claim 1, characterized in that: The dispersant is at least one of sodium polyacrylate, polycarboxylate, polyether dispersant, polyethylene glycol dispersant, and anionic surfactant.

5. The low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method as described in claim 1, characterized in that: Includes the following steps: A. Preparation of ceramic ink Fine hexagonal boron nitride powder was pre-dispersed in deionized water, followed by the addition of binder and dispersant. After being mechanically stirred and mixed evenly, the mixture was transferred to a ball mill for dispersion treatment to obtain a uniform and stable hexagonal boron nitride ceramic ink. The ball milling speed was 200–400 r / min; the ball milling time was 2–6 h. The resulting ceramic ink was then subjected to vacuum degassing for 10–30 min to remove internal air bubbles. B. Ink-to-Write 3D Printing The prepared hexagonal boron nitride ceramic ink is loaded into an ink direct writing 3D printing device and three-dimensional structure is formed by air pressure extrusion. Printing parameters include: nozzle diameter: 0.2~0.6mm; printing pressure: 0.1~0.5MPa; printing speed: 5~20mm / s; layer thickness: 0.1~0.4mm. After printing, a hexagonal boron nitride ceramic green body is obtained. C. Drying and low-temperature sintering The printed ceramic green body is dried and then degreased and sintered. The drying temperature is 40–80℃; the drying time is 6–24 hours. The sintering process includes: First stage: Raise the temperature from room temperature to 400-600℃ at a rate of 1-3℃ / min and hold for 60-180min; The second stage involves heating from 400–600℃ to 800–1000℃ at a rate of 0.3–2℃ / min and holding for 60–240 min. The temperature is then naturally cooled to room temperature to obtain a low-temperature densified hexagonal boron nitride ceramic structural component.

6. The low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method as described in claim 1, characterized in that: The hexagonal boron nitride ceramic ink has shear-thinning rheological properties, exhibiting high viscosity at low shear rates and decreasing viscosity at high shear rates, thus meeting the requirements for extrusion printing.

7. The low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method as described in claim 1, characterized in that: During the sintering process, the fine hexagonal boron nitride particles increase the particle contact area, enhance interfacial diffusion behavior, and promote the formation of sintering necks, thereby improving the densification of the ceramic structure and enabling the hexagonal boron nitride ceramic to obtain a stable structure in the temperature range of 800–1000℃.

8. The low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method as described in claim 1, characterized in that: The prepared hexagonal boron nitride ceramic structural components include at least one of the following: honeycomb structure, lattice structure, porous thermal insulation structure, complex curved surface structure, and thermal management structure.

9. The low-temperature densification hexagonal boron nitride ceramic ink and its direct-write 3D printing preparation method as described in claim 1, characterized in that: The prepared hexagonal boron nitride ceramic structural parts have a relative density of over 80% and a bending strength of over 30 MPa.